2020
DOI: 10.1097/md.0000000000019550
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of cage nonunion after anterior cervical discectomy and fusion

Abstract: The aim of our study was to explore risk factors of cage nonunion after anterior cervical discectomy and fusion (ACDF). 295 patients underwent ACDF in our hospital between Jan. 2014 and Jan. 2017. Of them, 277 patients suffered cage union (union group, UG) after 6-month follow-up and 18 did not (nonunion group, NG). We collected possible factors including gender, history of smoking, alcohol, hypertension, heart disease, diabetes, body mass index, diagnose, and preoperative visual analog scale -neck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 13 publications
0
23
2
Order By: Relevance
“…[ 25 ] Bao et al discovered that the angle of C2–C7 and T1 slope was all risk factors for nonunion of cage following ACDF. [ 8 ] In our study, we found that the angle of C2 to C7 (OR = 1.53, P < .001) was a significant predictor of nonunion. While, there was no significant difference between nonunion and union group in C2–C7 ROM, T1 slope and C2–C7 SVA.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…[ 25 ] Bao et al discovered that the angle of C2–C7 and T1 slope was all risk factors for nonunion of cage following ACDF. [ 8 ] In our study, we found that the angle of C2 to C7 (OR = 1.53, P < .001) was a significant predictor of nonunion. While, there was no significant difference between nonunion and union group in C2–C7 ROM, T1 slope and C2–C7 SVA.…”
Section: Discussionmentioning
confidence: 51%
“…[ 19 ] However, Bao and Van found no statistical difference between 1-level and 2-level ACDF. [ 8 , 20 ] In our study, we found that the rate of nonunion in cases with 3-level ACDF was 1.32-fold compared with 1-level.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Nonunion is a known complication of ACDF with a reported rate of about 5 percent. 28,29 A systematic review by Karikari et al 3 found no significant differences in fusion rates based on cage subsidence. Since subsidence causes a compounding effect in multilevel cervical fusions, it is possible that cage subsidence in multilevel fusions increases the risk of nonunion.…”
Section: Discussionmentioning
confidence: 99%